(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Fuzzy logic gives a system to model vulnerability, the human state of mind, thinking, and the discernment procedure. A fuzzy master system is just a specialist system that uses an accumulation of fuzzy membership capacities and rules, rather than Boolean logic, to reason about data. Fuzzy rules are the foundation of fuzzy logic systems. The Fuzzy Logic or the Fuzzy Logic Control is an Artificial Intelligence approachmethod, which is particularly utilized for designing and creating wise controlling frameworks. It gives a compelling and proficient strategy to recreate the human reasoning and practices so as to guarantee the related smart controlling structure. In this unique situation, this paper presents the FL-LAB v2 a software framework, which can be utilized to design and create various types of Fuzzy Logic derivation and controlling frameworks, by utilizing a simple to-utilize, interactive and compelling software condition.